Optimization of the Preparation Process of Flavonoid Solid Beverage from Ficus hirta Vahl. - Lin YANG; Shanyan ZHAO; Fan YANG; Hangying ZHANG; Bocheng HUANG; Juncheng ZHANG (Shipin gongye ke-ji)
In order to study the preparation process of Ficus hirta flavone solid beverage, ethanol was used as a solvent and ultrasonication was assisted to extract flavone. The extraction process of flavone was optimised by single factor experiment and response surface experiments, and the flavone species in the extract were determined by high performance liquid chromatography mass spectrometry (HPLC-MS/MS). Finally, the solid beverage of Ficus hirta flavone was prepared. The experimental results showed that the optimal conditions for the ultrasonic extraction of Ficus hirta flavone were as follows: Ethanol concentration of 72%, liquid-solid ratio of 40:1 (mL/g), and ultrasonic time of 32 min, and the total flavone extracted under this process condition was measured to be 9.016 mg/g. A total of 32 flavones were detected in the purified Ficus hirta, including 24 flavonoids and 8 isoflavonoids. Before and after the purification of Ficus hirta flavone, the DPPH and ABTS+ scavenging rate IC50 decreased from 0.678 mg/mL and 0.501 mg/mL to 0.179 mg/mL and 0.191 mg/mL, respectively. The reducing power of Ficus hirta at a concentration of 1.0 mg/mL was increased from 0.066 before the purification to 0.228 after the purification. The Ficus hirta solid beverage prepared by adding 20% sugar, 0.06% citric acid, and 2.5% maltodextrin had the highest sensory evaluation score, which provided guidance for the development and utilization of functional products of Ficus hirta.